ANALISIS FAKTOR-FAKTOR MOTIVASI PRA LANSIA TERHADAP OLAHRAGA BOLAVOLI PADA CLUB MELATI PUTIH KAMAL BANGKALAN - MUHAJIR AMRULLAH, MOH; SULISTYARTO, SONI (Jurnal Kesehatan Olahraga, 2019)
Abstract Lack of exercise in pre-elderly is caused by there is no motivation of pre-elderly to exercise volleyball. The phenomenon show that pre-elderly rare have motivation from their self to get exercise in volleyball for pre-elderly. Pre-elderly will have a good effect on body health by physical movements in Volleyball sport. This study aims to determine the motivation factors of pre-elderly on volleyball exercise at Melati Putih Kamal Club of Bangkalan. The type of research used is descriptive qualitative approach. In this study the samples are all pre-elderly members at Melati Putih Kamal Club of Bangkalan as many as 30 people. The sampling technique used is the Total Sampling technique. Instrument in this study is questionnaire and observation. The results of the study concluded that intrinsic factors have a higher average score where the intrinsic factor covers indicators of exercise, maintaining health, refreshing and eliminating saturation. Proven from descriptive analysis of the results of the study of pre-elderly intrinsic factors on volleyball exercise at Melati Putih Kamal Club of Bangkalan on average is 3.1 with the achievement level of 78.12% and it is in the very good category and the results of study based on pre-elderly extrinsic factors on volleyball exercise at at Melati Putih Kamal Club of Bangkalan, the average is 2.8 with the achievement level of 70.80% and it is in good category. Keywords: Motivation, Sports, Volleyball, Pre-Elderly.